Jorge M. Katz. Production functions, foreign investment and growth : a study based on the Argentina manufacturing sector, 1946-1961. Amsterdam ; North Holland : [S. L.], 1969. 203 p. - Bazdresch Parada, Carlos (Estudios Demográficos y Urbanos, 1971)
JORGE M. KATZ, Production Functions, Foreign Investment and Growth. A Study Based on the Argentina Manufacturing Sector, 1946-1961, Amsterdam, North Holland, 1969.